Skidding Analysis of Exhaust Cam-Roller Unit in the Steady/Startup Operation of Internal Combustion Engine - Shuyi Li; Feng Guo; Pat Lam Wong; Peng Liang; Jisong Huang (Lubricants, 2023)
This paper develops a coupling model of cam-roller contact and roller-pin contact considering thermal effects based on the exhaust cam-roller unit of an internal combustion engine. For the steady/startup running processes, the skidding and the lubrication performance are obtained in a complete cam rotation cycle, and the effects of oil viscosity or modified load are also discussed. The results show that the most significant effect of skidding on the cam-roller unit is the increase in friction between the cam and the roller. In a cam rotation cycle, the slide-roll ratio is not constant, and its value may even be negative. Compared with the steady running process, skidding is more pronounced during the startup running process, especially at the beginning of the acceleration stage (0–18°). Reducing oil viscosity or increasing modified load can effectively reduce the skidding situation, and its effect is more obvious in the steady running process than in the startup running process.